RELATIONSHIP BETWEEN PARENTING BELIEFS AND PRACTICES OF PARENTS WITH YOUNG CHILDREN - Solís Cámara Reséndiz, Pedro; Díaz Romero, Marysela; Díaz Romero, Marysela (Anales de Psicología / Annals of Psychology, 2007)
Most research has abandoned the attempt to establish direct associations between parenting beliefs and practices. In the present study, these relationships were assessed in a sample of 275 parents with young children. The selected instruments were specifically designed for measur-ing parenting beliefs or practices. Differences were found for parents’ gender and children’s sex. More beliefs-practices correlations were found for mothers. Beliefs-practices correlations were more similar between mothers and fathers of girls, than for those with boys. Main beliefs for mothers were: communication, parental support, role orientation, limit setting, and autonomy, and these beliefs were mainly related with disci-pline and nurturing practices. Main beliefs for fathers were: limit setting, role orientation, and parental support, and they were mainly related with discipline practices. The authors highlight the possible meanings of differ-ent relationships between parenting beliefs and practices, and argue for the inclusion of both parenting beliefs and practices in parenting research studies.